2018
DOI: 10.3390/ma11081481
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Evaluation of Preparing Asphalt Mixture with Low-Grade Aggregate, Rubber Asphalt and Desulphurization Gypsum Residues

Abstract: Road construction consumes great amounts of high-grade natural resources. Using low-grade natural rocks or some solid wastes as substitute materials is a hot topic. Considering this, the feasibility of using low-grade granite aggregate, solid waste-based filler (desulphurization gypsum residues, DGR) and binder (waste tire rubber modified asphalt, RMA) simultaneously in asphalt mixtures has been fully investigated in this research. The commonly used base asphalt and limestone powder (LP) filler were control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…e fitting results are also shown in Figure 5, and Figure 5(h) shows the variation of the exponential decay rate (damping coefficient ε r ) with the content of diatomite and basalt fibers. As can be seen from Figure 5, the correlation coefficients R 2 of exponential equation (12) for fitting the envelopes of vibration acceleration attenuation of seven groups of WRM are greater than 0.97, which shows that the exponential equation can well characterize the vibration attenuation of these asphalt mixtures. According to the fitting results of the damping coefficients ε r , it can be calculated that, compared with WRM, the damping coefficient ε r of DWRM with 5 wt.%, 7.5 wt.%, and 10 wt.% diatomite and BWRM with 0.2 wt.%, 0.3 wt.%, and 0.4 wt.% basalt fibers increases by 40.22%, 104.37%, 152.01%, 101.21%, 183.14%, and 216.02%, respectively.…”
Section: Vibration Attenuation Analysis Of Wrmmentioning
confidence: 87%
See 2 more Smart Citations
“…e fitting results are also shown in Figure 5, and Figure 5(h) shows the variation of the exponential decay rate (damping coefficient ε r ) with the content of diatomite and basalt fibers. As can be seen from Figure 5, the correlation coefficients R 2 of exponential equation (12) for fitting the envelopes of vibration acceleration attenuation of seven groups of WRM are greater than 0.97, which shows that the exponential equation can well characterize the vibration attenuation of these asphalt mixtures. According to the fitting results of the damping coefficients ε r , it can be calculated that, compared with WRM, the damping coefficient ε r of DWRM with 5 wt.%, 7.5 wt.%, and 10 wt.% diatomite and BWRM with 0.2 wt.%, 0.3 wt.%, and 0.4 wt.% basalt fibers increases by 40.22%, 104.37%, 152.01%, 101.21%, 183.14%, and 216.02%, respectively.…”
Section: Vibration Attenuation Analysis Of Wrmmentioning
confidence: 87%
“…Using waste tires rubber (WR) in road engineering materials can not only protect the environment and save resources but also improve the mechanical properties of pavement materials and reduce vibration and noise on the road [2,[5][6][7][8][9]. Some studies pointed out that the addition of WR to the asphalt mixtures could improve the performance of antideformation at high temperature and anticrack at low temperature [6,[10][11][12]. And WR also enhanced the hightemperature performance of desulphurization gypsum residues modified asphalt mixtures [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides WMA technologies, several materials such as recycled glass [28], fly ash derived zeolites [29], boron waste [30], recycled ceramic aggregates [31], desulphurization gypsum residues [32], and recycled polymers [33] have been investigated as asphalt additives or road base materials. Crumb rubber modified (CRM) represents a valuable solution to fulfill high environmental standards.…”
Section: Introductionmentioning
confidence: 99%
“…Andrzejuk et al [33] and Ogrodnik et al [34] reported their research on reusing the wastes of sanitary ceramics as aggregates for asphalt mixture and cement concrete, respectively. Waste concrete powder [35], low-grade aggregate [36], crumb rubber waste [37], and recycled concrete aggregate [38] were also successfully reused as construction materials. In the study by Li et al [39], the reclaimed asphalt pavement was reused 100% in cold recycled asphalt mixtures.…”
mentioning
confidence: 99%